Compliance Analysis of Environmental Management and Monitoring of Hydropower Plant in East Java - Kusuma Praend Adidarma; Arief Rachmansyah; Aminudin Afandhi (Postgraduate School Universitas Brawijaya, 2022)
Environmental documents (AMDAL and UKL-UPL) function as instruments in efforts to prevent environmental damage, but industry owners still need to carry out environmental management and monitoring properly, especially for hydropower activities in East Java Province. Moreover, supervision conducted by the government could have been more optimal. This is indicated by leadership that began in 2017 to 2019. In addition, there are discrepancies between environmental documents that are owned reality. This study analyzes industry owner’s compliance levels in implementing environmental documents. The study used an observative method with a prescriptive analysis approach based on qualitative data. The results showed that most industry owners still needed to obey, so alternative policies were required. The recommended alternative is to adjust the environmental documents with direction and coordination from the relevant government agencies based on the constraints faced to increase compliance with the implementation of environmental monitoring.